Efektivitas Rezim Liberalisme Penanaman Modal Asing Langsung Dalam Bank Dunia Terhadap Perubahan Perilaku Negara Anggota Studi Kasus Indonesia (1998 â 2002) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT The World Bank imposes regime of foreign direct investment (FI)I) to its member countries especially which is affected by economic crisis and proposes to borrow money from the Bank. The Bank encloses the regime in the scheme of structural adjustment loans (SAL) in which the borrowing country should propose a list of policy reform programs in a letter of development (LoD) and it can not do other than the agenda stated on the list. Studying Indonesia as one of SAL borrowers the author finds that the FDI inflow to the country in 1998 - 2002 was constantly decreasing. The fact lifts question on the effectiveness of the regime. The author analyzes regime effectiveness as an outcome, not as an output or an impact, specifically in behavioral change. He finds that the regime is relatively effective in Indonesia, meaning there is significant behavioral change but it is not a truly major improvement. The effectiveness is in level 3 of 0 - 4 scale.